PENGARUH PEMBELAJARAN PROJECT BASED LEARNING BERINTEGRASIKAN SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS (STEM) TERHADAP HASIL BELAJAR GEOGRAFI DI SMA NEGERI 1 GORONTALO - Novia Ayu Lestari; Sunarty Suly Eraku; Rusiyah Rusiyah (Universitas Negeri Gorontalo, 2021)
The influence of science, technology, engineering, and mathematics (STEM) Integrend Learnig Process on the Learning Outcomes of 1 th Grade Student (An Experimental Research Implementend in SMA 1 State Senior High School if Gorontalo). This study aimed to determine the differences in learning outcomes of student with the implementation of the Ppa-STEM learning model whilw the control class implemented the learning cycle (5E) learning model on the topic of “population planning and Development Dynamis in Indonesia”. To achieve these objecives, this research employed experimental design with post-test Control Group Design. Data collection techniques involved learning result test, which was provided towards the sample of research. The sample of the study consisted of two classes; class XIb3 of social science as the control class employed the learning cycle (5E) model. During the hypothesis testing, the homogeneity and normality test of the data was conducted in order to conduct hypothesis testing by using parametric statistics. The data normality test employed a chi-square statistical test of the pair of null hypothesis Ho and its match Hi with α = 0,05 significal rate. The test result showed that χ2count less than χ2table for the experimental class with 3,449 less than 11,070 and the control class of 1,023 less then is 9,488. The result revealed that the two data classes can be normally distributed. Based on the results of normality test data, the average score pg students learning outcomes used the statistical test. The hypothesis test results obtained tcount greater than ttable which was 6,58 greater than 2,02. All in all, the results revealed that there were differences in the learning outcomes of students who used the two aforeentioned learning models.